Precipitation characteristics over Paradeep - SIVARAMAKRISHNAN , T. R.; PRASAD, J. R. (MAUSAM, 1998)
The daily rainfall records since 1976 and the SRRG records after its installation in 1982 at Paradeep have been analysed and rainfall climatology has been worked out. The heaviest 24-hour rainfall recorded at the station is 264 mm on 4 June 1982. The mean annual rainfall is 1475 mm. January and December are near dry months while August is the wettest month getting about 339 mm rainfall. The variability of annual rainfall here is 20 %. Light rainspells giving a total rain of 10 mm or less form about 50% occasions in pre-monsoon period and 63% of occasions in monsoon period. The extended rainspells lasting for more than 4 hours form about 10% of occasions in pre-monsoon season and 6% occasions in monsoon season. While morning (04-08 hr IST) period gets the rainfall in both pre-monsoon and monsoon months, early night gets the peak rainfall activity during the pre-monsoon months.